The echocardiographic assessment of left ventricle diastolic function in Olympic-class athletes - Braksator, W.; Krol, W.; Mamcarz, A.; Krol, K.; Wrzosek, K.; Kuch, M.; Dluzniewski, M.; Krysztofiak, H. (European Journal of Echocardiography, 2006)
Introduction: Echocardiography is a basic tool in assement of heart`s morphology and function I elite athlethes. However, there are not many papers concerning diastolic function in this specific group. Aim of the study: The aim of the study was to assess left ventricle diastolic function in Olympic-class athletes using conventional Doppler imagining and Tissue Doppler Imagining (TDI). Materials and methods: 85 proffesional athletes took part in a study. Most of them were mebers of Polish Olympic Team (Athens 2004). There were 24 women and 61 men in examined group. A single transthoracic echocardiographic examination has been performed in time of very intensive training. Mitral inflow velocity profile was assessed using pulsed Doppler imaging. Deceleration time (DT), duration of isovolumetric relaxation time (IVRT), maximal velocity of early (E) and atrial (A) phase and their ratio were estimated. Velocity of septal part of mitral annulus was assessed using TDI in four chamber apical view during early (E`) and atrial (A`) phase. Results: There was no single case of impaired LV diastolic function in examined group, however some parameters exceeded normal values for healthy people (CCS). E/A ratio<1 was not observed but in 56,7% of examined it exceeded 2. In 50.6% examined with E/A ratio >2 E/E` ratio was >8 but with normal velocities of mitral annulus in TDI it may indicate dynamic diastolic function, paradoxically. IVRT was longer then 92 ms in 24% casese and DT exceeded norms (150-200 ms) in 56% examined but without reversed E/A ratio (<1) this alteration does not indicate impaired relaxation. In examined with high E/A ratio (>2) LVEDd (2.8 cm/m2 vs 2.67 cm/m2 p<0.02), IVSd (0.58 vs 0.55 p<0.02) and LV mass (128.5 g/m2 vs 118.4 g/m2 p<0.05) was significantly higher then in those with normal E/A ratio. In case of other parameters exceeding norms no significant differences in morphology of LV were observed. Conclusions: 1. Impaired relaxation of LV was not observed even in individuals with hypertrophic heart muscle in examined group. 2. Some parameters (E/A>2, E/E`>8), which in ill individuals indicate advanced diastolic dysfunction (restriction), in proffesional athletes seems to show normal, dynamic relaxation. 3. High E/A ratio is connected with more advanced state of physiologic heart muscle hypertrophy. 4. Alteration of LV diastolic parameters should be observed in long-term.